(1126) aggregate econometric models for projection of demand on steel نماذج اقتصادية قياسية إجمالية لتوقع الطلب على الصلب - montaser, saadia (the institute of national planning, 2018)
in this study steel consumption was related to several national parameters in several econometric models. assumption tests and results of the models, as used in forecasting, combined with an evaluation of each model, and also modification of results given by the model.